Mudharabah: Praktik perhitungan bagi hasil pada sukuk ritel dalam ekonomi syariah - Purnomo, Agus; Zahra Maulida, Atika; Hadi, Abdul (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
Capital market transaction activities encourage the country's economic growth through the investment sector of Sharia capital market products and Sharia capital market portfolios traded by companies through Sharia capital market transactions. The research explains the practice of calculating income in retail sukuk products, corporations, and savings sukuk that use mudarabah contracts. The government issues securities to obtain funds and manages to get profits that will be distributed to investors with the principle of mudarabah contracts. The research aims to discover the practice of calculating retail sukuk profit sharing, selling retail sukuk, and implementing retail sukuk in the Sharia economy. The research method uses a qualitative method, using primary data from financial reports from the BI website. In contrast, secondary data is taken from books, journals, scientific papers, final projects, and others. The results of this research are retail sukuk issued with auction mechanisms, book-building, and private placement. There are several stages for retail sukuk sales and several stages for the implementation of sukuk. The shared practice of calculating the profit sharing applied the Sharia principles: 60%: 40%, 70%: 30%, and 50%: 50%. In 2022, the Sharia capital market distributed a surplus of IDR 175 billion.